RITUAL AGAMA HINDU DALAM MEMBUDAYAKAN NILAI-NILAI KEARIFAN LOKAL - Aryanatha, I Nengah (Institut Hindu Dharma Denpasar, 2018)
Before Hinduism entered the archipelago, there were many local beliefs. Some of these types of local beliefs are Animism. Animism is basically a belief in the spirits that inhabit the universe around human habitation, is the oldest religious form. In this paper the author tries to examine the role of religion in cultivating the values of Hindu wisdom from prehistoric times to the development of culture in modern times. After going through an indepth analysis, a conclusion can be drawn about the Ritual Role of Religion in Cultivating Hindu Wisdom Values, namely having a primary role in understanding and implementing the teachings of Hinduism which is based on culture (local wisdom) so that culture and religion synergy in social life society, social religion and social culture.